2020
DOI: 10.1186/s12875-020-01232-8
|View full text |Cite
|
Sign up to set email alerts
|

Does GP empathy influence patient enablement and success in lifestyle change among high risk patients?

Abstract: Background: Chronic lifestyle-related-diseases can be prevented by healthy lifestyle. Patients at high risk of disease may benefit from targeted health checks in general practice. However, general-practice-based-studies have shown that patient outcome, enablement, and well-being may be influenced by general practitioner (GP) empathy. The aim of this study is to investigate 1) how high risk patients evaluate their GPs' empathy during a health check consultation, 2) whether the perceived GP empathy is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…The findings of the current study showed that, following clinical consultation, the enablement and satisfaction scores of the sample were slightly more than half of the study subjects were low. This result corroborates the idea of Hansen et al [30] who mentioned the same result. While this result was inconsistent with Tolvanen et al [18] in Finland who mentioned that more than half of the studied patients had a moderate level of enablement and satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the current study showed that, following clinical consultation, the enablement and satisfaction scores of the sample were slightly more than half of the study subjects were low. This result corroborates the idea of Hansen et al [30] who mentioned the same result. While this result was inconsistent with Tolvanen et al [18] in Finland who mentioned that more than half of the studied patients had a moderate level of enablement and satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…This result corroborated the idea of (Hansen et al 2020) entitled "Does GP empathy influence patient enablement and success in lifestyle change among high-risk patients?" Who mentioned the same result?…”
Section: Discussionsupporting
confidence: 80%